2016
DOI: 10.7554/elife.18134
|View full text |Cite
|
Sign up to set email alerts
|

HID-1 is required for homotypic fusion of immature secretory granules during maturation

Abstract: Secretory granules, also known as dense core vesicles, are generated at the trans-Golgi network and undergo several maturation steps, including homotypic fusion of immature secretory granules (ISGs) and processing of prehormones to yield active peptides. The molecular mechanisms governing secretory granule maturation are largely unknown. Here, we investigate a highly conserved protein named HID-1 in a mouse model. A conditional knockout of HID-1 in pancreatic β cells leads to glucose intolerance and a remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 78 publications
1
36
2
Order By: Relevance
“…There are several steps in DCV maturation that involve membrane fusion reactions that may require tethering molecules. One is the homotypic fusion of immature DCVs, a process recently shown to involve the HID‐1 protein . Interestingly, hid‐1 mutants in C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several steps in DCV maturation that involve membrane fusion reactions that may require tethering molecules. One is the homotypic fusion of immature DCVs, a process recently shown to involve the HID‐1 protein . Interestingly, hid‐1 mutants in C .…”
Section: Discussionmentioning
confidence: 99%
“…One is the homotypic fusion of immature DCVs, 4,18,46 a process recently shown to involve the HID-1 protein. 47 Interestingly, hid-1 mutants in C. elegans have defects in locomotion and DCV cargo sorting similar to cccp-1 and rab-2 mutants, 21,48,49 suggesting that RAB-2 and CCCP-1 may also be important for homotypic fusion of immature DCVs. Also, a recent human exome-sequencing project identified probably causative mutations in the human orthologs of hid-1 and cccp-1 in two people with a range of similar neurological symptoms.…”
Section: What Is the Function Of Cccp-1 In DCV Biogenesis?mentioning
confidence: 99%
“…Ortolá, Topalidou et al, 2019), suggesting that they both act at a post-Golgi step during DCV maturation. This is in contrast to other known regulators of DCV biogenesis such as PICK1, ICA69, and HID-1 that are needed to control the budding of immature DCVs from the TGN and whose loss leads to a defect in the processing of proinsulin to insulin (Cao, Mao, et al, 2013;Holst, Madsen, et al, 2013;Du, Zhou, Zhao, Cheng, et al, 2016;Hummer et al, 2017). Our findings suggest that EIPR1 and CCDC186 act at a later step in DCV biogenesis than PICK1, ICA69, and HID-1.…”
Section: Interestingly Eipr1 Ko Cells Have Similar Defects As Ccdc18mentioning
confidence: 55%
“…More recently, it has been reported that conditional KO mice, in which HID-1 has been specifically inactivated from beta-cells of the pancreas, display impaired insulin secretion. This phenotype has been attributed to a defect in homotypic fusion of immature insulin granules (Du et al, 2016), a mechanism that is somewhat surprising considering that this fusion process had never been previously observed in this cell type. Although we cannot definitively rule out that this might contribute to our phenotype, we did not observe any obvious defects in LDCV homotypic fusion in our HID-1 KO PC12 cells by electron microscopy.…”
Section: Discussionmentioning
confidence: 85%
“…A forward genetic screen in the model organism C. Elegans has previously identified HID-1 as a factor implicated in neuropeptide sorting and secretion (Mesa et al, 2011). HID-1 null worms display reduced levels of LDCV soluble cargo and impaired neurosecretion (Mesa et al, 2011, and conditional knockout (KO) mice lacking HID-1 in beta-cells of the pancreas display a defect in insulin secretion (Du et al, 2016), suggesting that this factor might be significant for glucose homeostasis. Interestingly, HID-1 is a peripheral membrane protein associated with the Golgi/TGN and its expression seems restricted to specialized secretory cells , suggesting that it might directly contribute to LDCV biogenesis.…”
mentioning
confidence: 99%